PENGOLAHAN LIMBAH UKM SULAM PITA UNTUK BAHAN BAKU PRODUK FASHION - Yunita Fitra Andriana; Ulfa Septiana; Rizki Kurniawan (Universitas Pendidikan Indonesia, 2017)
Ribbon embroidery is a technique to decorate fabric by sewing ribbon on surface of the fabric using a variety of decorative piercing techniques. The advantage of this technique is the size of ribbon that wider than the yarn, so it can produce three-dimensional decoration with varied designs and colors. The process of producing products with ribbon embroidery brings out wastes, that has not been treated well. The wastes consists of pieces of ribbon, yarns with varying sizes and different colors, and also pieces of fabrics. To reduce the amount of waste production process, 3R principle can be applied, reduce, reuse, and recycle. The principle of recycle can be used to produce new alternative materials by processing ribbon embroidery industry, so as to reduce the amount of waste, it also increase creativity in producing new products that environmentally friendly. This research explores various techniques to process ribbon embroidery industry waste, so it can be reused as an alternative textile raw material This research begins with collecting data through observation and interviews to the ribbon embroidery industry in Limo Village, Depok to know the production process of the industry and to find out the amount of waste that has been produced during the process. The next step is processing the ribbon embroidery industry waste with various types of exploration techniques to produce new alternative of textile raw materials. Moreover, the raw materials will be processed into eco-fashion products that highly aesthetic and valuable.